(untitled) (Al-Academy, 2025)
This research addresses the aesthetic study of smart children’s product interfaces and their effective use. It is considered one of the modern innovations in the field of product design aimed at this demographic. The research focuses on the individual and multiple aesthetics in the design of these product interfaces and how the aesthetics of smart product interfaces affect the user experience. It also discusses how to integrate aesthetics into smart children’s products in a way that makes their interfaces user-friendly, allowing for interaction, such as controlling sound or movement, among other features. The research problem lies in how to incorporate aesthetics into the interfaces of smart children’s products, summarized by the following question: What are the aesthetics of smart children’s product interfaces and their effectiveness on user experience? The importance of the research aims to attract users to the industrial product and highlight aesthetics as a method to draw attention to the interfaces of smart products. The theoretical material includes a study of the aesthetics of smart children’s product interfaces, their types, and their effectiveness in use.